2022
DOI: 10.3390/ijms232012394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the NAC Transcription Factors and Their Function in ABA and Salinity Response in Nelumbo nucifera

Abstract: Nelumbo nucifera Gaertn. is an important perennial aquatic herb that has high ornamental, edible, medicinal, and economic value, being widely distributed and used in China. The NAC superfamily (NAM, ATAF1/2, CUC2) plays critical roles in plant growth, development, and response to abiotic and biotic stresses. Though there have been a few reports about NAC genes in lotus, systematic analysis is still relatively lacking. The present study aimed to characterize all the NAC genes in the lotus and obtain better insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Thus, the three WRKY TFs might play multiple roles in the response to saline-alkali stress in birch plants. Some studies have shown that NAC, ERF, and bHLH TFs can respond to various types of abiotic stress in plants [22][23][24][25][26]. In our study, the expression of NAC9, ERF019, and bHLH162 was upregulated in the 3 h NaHCO 3 treatment but down-regulated in the 6 h NaHCO 3 treatment, relative to the control.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, the three WRKY TFs might play multiple roles in the response to saline-alkali stress in birch plants. Some studies have shown that NAC, ERF, and bHLH TFs can respond to various types of abiotic stress in plants [22][23][24][25][26]. In our study, the expression of NAC9, ERF019, and bHLH162 was upregulated in the 3 h NaHCO 3 treatment but down-regulated in the 6 h NaHCO 3 treatment, relative to the control.…”
Section: Discussionsupporting
confidence: 52%
“…Most plant NAC family genes were obtained by screening, which has laid an important foundation for NAC gene function studies [61][62][63][64]. Studies have demonstrated that NAC transcription factors play an essential role in plant growth and development [65], stress response [66], fruit development [9], plant senescence [67] and fruit ripening [9,61].…”
Section: Discussionmentioning
confidence: 99%
“…Most NAC TFs are localized in the nucleus, representing their active forms, where they bind DNA and carry out specific transcriptional roles [4,48,[58][59][60][61]. However, a subset of NACs is found in other cellular compartments such as the plasma membrane (PM), cytoplasm, or endoplasmic reticulum (ER), indicating inactive forms (i.e., dormant state) (Figure 2).…”
Section: Unraveling the Complex Molecular Nac Structurementioning
confidence: 99%